EXISTENTIAL CRISIS AS MANIFESTED IN ANEES SALIM’S THE ODD BOOK OF BABY NAMES - JEBA SUBITHA , DR. J. SUBITHA PERSIS (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
The paper entitled Existential Crisis as manifested in the novel The Odd Book of Baby Names by Anees Salim delves into the fundamental aspects of existentialism and its impact on human existence. Existentialism prioritizes the importance of individual existence, freedom, and choice, as well as the responsibility that comes with it. It explores the human condition and the questions surrounding the meaning and purpose of life. Human beings live their life with family, friends, and loved ones, while these relationships provide a sense of purpose and fulfillment. When these connections are threatened through the loss of a parent or loved one, it can shatter the very foundation of a person’s life. The loss of a parent leads to an existential crisis by challenging one’s identity, purpose, and role in the world. In such a crisis, a person may begin to question his own existence, feeling as though his life lacks meaning and significance. The characters in The Odd Book of Baby Names struggle with the loss of their parents and their search for identity. Without a clear sense of identity, they may feel excluded from society. The sense of disconnection from themselves and others can lead to profound loneliness and a sense of meaninglessness.